Show me your body and I tell you how hold you are: a non-invasive methodto define 6 life history-classes in Risso's dolphins (Grampus griseus), using an identified trial population in the Atlantic - Hartman, Karin L. (2013)
"[…]. The objective of this paper is to present a new non-intrusive and inexpensive method to classify six life history stages in Risso's dolphins: from newborn calf to old-adult. We propose an age-class indicator model using the scarification patterns and the species unique discoloration process. We developed two methods and tested these among 52 rankers to examine if our proposed methods could be applied by anybody and if they would conform with our age class model. We also investigated the possible differences in the scarification patterns between genders. We used a longterm followed identified population of Risso's dolphins in the Azores to set up our test methods and report our present results."